Tathbiq Thariqah Ta’lim Maharah al-Kalam min Mandzur Ibn Khaldun - Ahmad Azhari; Syuhadak Syuhadak; Bakri Muhammad Bakhiet (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2023)
The purpose of this research is to describe the application of the Maharah Kalam learning method from the perspective of Ibn Khaldun. In this research, the researcher used a qualitative approach with descriptive analysis methods. Data collection is done by: a) observation method; b) interview method; c) documentation method. While data analysis techniques 1) data collection; 2) data reduction; 3) data displays; 4) conclusion. The results of the research show that the application of the maharah al-kalam learning method at IAIN Palangka Raya has several elements, namely starting from the basics and repeating the material at the beginning of each meeting from the point of view of Ibnu Khaldun. This is what is called the Takrir and Tadarruj method. In maharah al-kalam learning which is implemented by lecturers, discussion sessions are also held between students and lecturers who also participate, according to Ibnu Khaldun this is called the Munaazarah method. Apart from that, in maharah al-kalam learning there is also an opportunity for students to experience experiences with other teachers and different places, and this according to Ibn Khaldun is called the Rihlah method.